Première session du " Synode sur la synodalité ": une relecture théologique - Rougé, Matthieu (Nouvelle revue théologique, 2024)
As a member of the 16th Ordinary General Assembly of the Synod of Bishops devoted to synodality, the Bishop of Nanterre discusses the debates of the October 2023 assembly and shows the dogmatic and pastoral challenges of the resulting report. Against the temptations of "neo-Marcionism, neo-Joachimism or neo-Bellarminism", he proposes a dialectic of love and truth expressed in the missionary dialectic of dialogue and proclamation.